2015
DOI: 10.1186/s12888-015-0523-9
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatising attitudes of undergraduates towards their peers with depression: a cross-sectional study in Sri Lanka

Abstract: BackgroundThere is limited research examining mental health-related stigma of undergraduates in non-western developing countries. This study examined stigma of undergraduates in Sri Lanka towards another depressed undergraduate.MethodsA hypothetical vignette of an undergraduate suffering from depression was presented. A total of 4650 undergraduates responded to scales assessing their personal stigma towards and desire for social distance from this individual. Exploratory structural equation modelling (ESEM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
(84 reference statements)
1
15
0
Order By: Relevance
“…This cross-sectional study was conducted from June to November 2013 among undergraduates at the University of Colombo, one of the largest universities in Sri Lanka [ 30 ]. The present paper, the Amarasuriya et al [ 24 ] paper examining depression among undergraduates in Sri Lanka and the Amarasuriya et al [ 25 ] paper examining stigma among this population, were all based on the same Depression Literacy Survey conducted among this undergraduate population at the University of Colombo.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This cross-sectional study was conducted from June to November 2013 among undergraduates at the University of Colombo, one of the largest universities in Sri Lanka [ 30 ]. The present paper, the Amarasuriya et al [ 24 ] paper examining depression among undergraduates in Sri Lanka and the Amarasuriya et al [ 25 ] paper examining stigma among this population, were all based on the same Depression Literacy Survey conducted among this undergraduate population at the University of Colombo.…”
Section: Methodsmentioning
confidence: 99%
“…Scores obtained on the Personal Stigma and Social Distance Scales (continuous variables) were also examined as predictors of the scale scores. Amarasuriya et al [ 25 ] found that the Personal Stigma Scale consisted of two dimensions of stigma (i.e., the “Weak-not-Sick” and “Dangerous- Undesirable” dimensions), and that the Social Distance Scale consisted of one dimension (i.e., the “Social Distance” dimension). Hence, the participants’ stigma scores on these measures were entered into the model in relation to the Weak-not-Sick, Dangerous-Undesirable and Social Distance scales that were constructed in relation to the identified dimensions of stigma (the latter scale being the same as the original social distance measure) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ] Another reason is the stigma or negative attitude towards people with mental disorders. [ 13 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…The portrayal of mental illness in the media has also had an impact on the public's understanding of mental health and issues related to stigma 10,11. Reviews of university students described significant prevalence of illness, suggesting the need for both recognizing mental illness and improving education regarding stigma 12,13. Rusch and colleagues14 described 3 types of stigma: negative stereotypes, prejudice with negative emotional reactions, and discrimination.…”
Section: Introductionmentioning
confidence: 99%